COVID-19 infection rate and time spent at home: analysis of the beginning of the pandemic - Vinícius Nagy Soares; Hélio Mamoru Yoshida; Daniel Eduardo da Cunha Leme; Ricardo Aurélio Carvalho Sampaio; Gabriel de Oliveira Rufino; Paula Teixeira Fernandes (Universidade de Santa Cruz do Sul, 2022)
Background and Objectives: Evidence suggests that the failure of epidemiological control impedes the resumption of socioeconomic activities.  Therefore, this study aimed to describe epidemiological aspects and the pattern of mobility on each continent and to verify the association between the COVID-19 infection rate and time spent at home. Methods: We analyzed reports from Global Positioning System of 97 countries and their epidemiological indicators until May 27, 2020. Results: Cases of COVID-19 ranged from 22 to 1,745,803, and deaths ranged from 0 to 102,107. The highest rates per 100,000 population were observed in Europe and America. Approximately 54% of COVID-19 cases occurred in America and 51% of deaths in Europe. Countries reduced mobility in retail and recreation (-43.45%±20.42%), grocery and pharmacy (-17.95%±20.82%), parks (-18.77%±37.34%), transit stations (-43.09%±20.31%), workplaces (-21.74%±19.92%), and increased time spent at home (13.00%±8.80%). Linear regression showed that European inhabitants stayed at home less when compared those on the American continent (β=-4.933, SE=0.976, p<.001). In addition, every unit increase in the infection rate per 100,000 population increased 0.005 points in the mean time spent at home (β=0.005, SE=0.001, p<.001). Conclusions: We provide evidence that increased infection rate of COVID-19 is associated with increased length of stay at home. As a main lesson, COVID-19 showed that in the absence of pharmacological resources, government authorities need to act quickly to contain the spread of infectious diseases.